Administrative Law and Public Service Delivery: Enforceability as the Decisive Variable in a Comparative Analysis of the European Union and Vietnam - Nguyen, Bich Ngoc; Van Vu, Tuan (Jambe Law Journal, 2026)
Public service delivery has become a key domain through which administrative law responds to contemporary challenges of governance, digitalization, and rising citizen expectations. However, existing scholarship has largely examined administrative law and public service delivery in isolation, leaving a gap in understanding how legal frameworks shape service outcomes in practice. This study addresses that gap by conceptualizing public service delivery as a functional site for analyzing administrative law and by identifying enforceability as a central explanatory variable. The article examines how administrative law shapes public service delivery through a comparative analysis of the European Union and Vietnam, focusing on legal principles, institutional arrangements, and governance mechanisms. Methodologically, it adopts a qualitative, law-centered comparative approach grounded in doctrinal analysis and structured through a thematic analytical framework. The analysis demonstrates that public service delivery in the European Union is embedded within a dense and enforceable administrative law framework, where legal principles, multi-level governance, and safeguards for digital administration enhance accountability, procedural fairness, and service quality. In contrast, Vietnam’s public service governance remains largely policy-driven. Although administrative law principles are formally recognized, their practical impact is constrained by limited judicial enforceability, particularly in digital and decentralized contexts. The study concludes that the decisive factor shaping public service delivery is not the formal recognition of administrative law principles, but their enforceability. Sustainable improvements therefore depend on consolidating administrative law as a rights-based and enforceable framework capable of aligning efficiency, digital innovation, and citizen-centric governance across diverse systems